PEMANFAATAN LIMBAH BUAH DAN SAYUR SEBAGAI ECO-ENZYME ALTERNATIF PUPUK DAN PESTISIDA SINTETIK DI DESA MELATIWANGI KECAMATAN CILENGKRANG KABUPATEN BANDUNG - Turmuktini, Tien (The IMPACT : Jurnal Pengabdian Kepada Masyarakat Universitas Islam As-Syafiiyah, 2024)
Synthetic pesticides are environmental pollutants that can cause pest resistance and can endanger human health. One alternative that can be used to replace synthetic pesticides is to use biopesticides. Biopesticides can be a solution because they are easily degraded, non-toxic and have a wider spectrum of activity. One way to get this biopesticide is to make Eco-Enzyme. Based on the results of KKN-PM activities that have been carried out regarding socialization and Eco-Enzyme training, it has had a impact on farmer groups and women farmer groups in Melatiwangi Village. Utilizing fruit and vegetable waste, if done well, can reduce agricultural waste and be useful for plant growth.